2019
DOI: 10.3389/fcvm.2019.00048
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-Immunology of Myocarditis: Focus on Immune Mechanisms and Treatment Options

Abstract: Myocarditis and inflammatory cardiomyopathy are syndromes, not aetiological disease entities. From animal models of cardiac inflammation we have detailed insight of the strain specific immune reactions based on the genetic background of the animal and the infectiosity of the virus. Innate and adaptive immunity also react in man. An aetiological diagnosis of a viral vs. a non-viral cause is possible by endomyocardial biopsy with histology, immunohistology and PCR for microbial agents. This review deals with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 108 publications
(117 reference statements)
0
77
0
2
Order By: Relevance
“…According to the European Society of Cardiology (ESC) myocarditis taskforce classification [17] and the current literature on FM [18], FM can be categorized into the histologically defined entities of lymphocytic, eosinophilic, and giant cell myocarditis and sarcoid heart disease. The lymphocytic forms are subdivided into those of infective and noninfective origin.…”
Section: Viral Fulminant Myocarditismentioning
confidence: 99%
“…According to the European Society of Cardiology (ESC) myocarditis taskforce classification [17] and the current literature on FM [18], FM can be categorized into the histologically defined entities of lymphocytic, eosinophilic, and giant cell myocarditis and sarcoid heart disease. The lymphocytic forms are subdivided into those of infective and noninfective origin.…”
Section: Viral Fulminant Myocarditismentioning
confidence: 99%
“…It has been suggested that pathophysiology of viral myocarditis begins with viral replication within the myocardium resulting in myocardial inflammatory injury, despite the presence of viral nucleic acid in only 30% of endomyocardial biopsies. 21 While it has been suggested that patients with severe cases of COVID-19 have high rates of cardiac dysfunction, it is our opinion that the absence of cardiac dysfunction does not necessarily rule out the absence of SARS-CoV-2 involvement of the myocardium. As discussed earlier, the ACE2 receptor is an entry point for SARS-CoV-2, which is also present within the cardiovascular system.…”
Section: Cardiacmentioning
confidence: 89%
“…Supporting this possibility, studies by endomyocardial biopsy for the definite diagnosis of myocarditis have provided evidence of inflammation and/or viral infection within the myocardium in patients with DCM, thus triggering the initiation or progression of myocarditis to postinflammatory DCM. Complementary to the recent reviews by Imanaka-Yoshida [1] and Maisch [2], this contribution examines molecular and clinical data of the progression from viral and autoreactive (nonviral) myocarditis to DCM and offers perspectives beyond mere heart failure management to a treatment of the underlying cause.…”
Section: Inflammatory Dilated Cardiomyopathy Etiology and Clinical Mamentioning
confidence: 96%
“…Dilated cardiomyopathy (DCM) is a heterogeneous group of myocardial diseases clinically defined by the presence of left ventriculardilatation and contractile dysfunction [1,2]. Using the broadest definition of DCM would make the disease equivalent to heart failure since it would alsoinclude cardiac dysfunctionaftermyocardial infarction and through remodeling.…”
Section: Inflammatory Dilated Cardiomyopathy Etiology and Clinical Mamentioning
confidence: 99%
See 1 more Smart Citation